Characteristics of Oklahoma Agritourism Facebook Posts - Brittany Bowman; Quisto Settle; Angel Riggs; Stacy Tomas; Audrey E. H. King (Journal of Applied Communications, 2020)
Agritourism is recreational travel for agricultural activities. While it provides many benefits, such as rural development and heritage preservation, many agritourism operators express challenges in marketing their operations. Social media is increasingly common in tourism marketing, but little research exists describing current marketing practices. Quantitative content analysis was used to describe 174 Oklahoma agritourism operations’ Facebook page activity in June 2018. Original posts created by the agritourism operations and community posts created by the general public had similar amounts of public interaction. Post interactions were not related to post length, and original post interactions were also not related to overall page likes. Live videos and traditional posts received the most interaction amongst types of original posts. Facebook event posts made by the agritourism operation received more public interaction than event posts made by the general public. Agritourism operators should focus on quality over quantity of information and be wary of creating posts in an “echo chamber” as only a small proportion of a large page following interact with posts. Marketing practitioners should avoid providing one-size-fits-all advice in Facebook marketing, as there was a large variety of Facebook activity observed. Future research should more specifically describe content of posts and consider perspectives of agritourism operators and visitors towards current Facebook marketing strategies.
Keywords: Facebook; agritourism; Excellence Theory; content analysis; marketing